2016
DOI: 10.1027/1614-0001/a000187
|View full text |Cite
|
Sign up to set email alerts
|

Personality of Clown Doctors

Abstract: Abstract. In recent years, both professional and volunteer clowns have become familiar in health settings. The clown represents a peculiar humorist’s character, strictly associated with the performer’s own personality. In this study, the Big Five personality traits (BFI) of 155 Italian clown doctors (130 volunteers and 25 professionals) were compared to published data for the normal population. This study highlighted specific differences between clown doctors and the general population: Clown doctors showed hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Actions such as these would be particularly effective during their early stages in the profession Moreover, humor can be learned, trained, or otherwise leveraged for organizational advantage [28]. Finally, although medical clown interventions have been shown to mitigate the negative effects of hospitalization and have a positive impact on both patients and medical staff [1,2,4 ], it seems that we need a better understanding of clowns' personality in order to integrate them in the healthcare delivery system. In their typical work experience, the medical clown performs alone and, in some cases, in a non-supportive environment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Actions such as these would be particularly effective during their early stages in the profession Moreover, humor can be learned, trained, or otherwise leveraged for organizational advantage [28]. Finally, although medical clown interventions have been shown to mitigate the negative effects of hospitalization and have a positive impact on both patients and medical staff [1,2,4 ], it seems that we need a better understanding of clowns' personality in order to integrate them in the healthcare delivery system. In their typical work experience, the medical clown performs alone and, in some cases, in a non-supportive environment.…”
Section: Resultsmentioning
confidence: 99%
“…To accomplish their goals, medical clowns are required to elicit smiles and laughter when interacting with patients, families, and medical staff [3,1]. Whereas recent studies have focused on the therapeutic bene ts associated with the use of medical clowns [2], very few studies have investigated the clowns' personal characteristics and behavior [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies of volunteers found other predictors of their psychological health, such as supportive work climate and autonomous motivation [ 64 ]. Other personality traits that characterize the Italian clown doctors, such as high agreeableness, conscientiousness, openness, extraversion, and low neuroticism [ 65 ], might also contribute to their psychological health. Therefore, further studies are needed to determine what could explain the remaining variance of psychological and subjective well-being.…”
Section: Discussionmentioning
confidence: 99%
“…The Fool, the Trickster, the Jester, the Joker, the Clown are all associated archetypal images (e.g. Dionigi, 2016; Harris, 2012; Nichols, 1974). Each possesses peculiar features, such as the Trickster’s inclination towards deceit 2 and the Jester’s towards the critique of power.…”
Section: Responsibility In Foolsmentioning
confidence: 99%